Kesetaraan Gender dan Perdamaian Global: Mendorong Partisipasi Perempuan dalam Negosiasi Perdamaian - Muhammad Firman; Sobali Suswandy; Denda Ginanjar; Melita Amalia Ratu Kania (Journal on Education, 2023)
This study aims to determine and analyze the copra business in Pesisir Selatan Regency in terms of: (1) the distribution pattern of the copra business, (2) the feasibility of the copra business in Pesisir Selatan District. This type of research is quantitative. This research was conducted in Pesisir Selatan District in three subdistricts namely Lengayang District, Ranah Pesisir District and Linggo Sari Baganti District. The sample of this study used a total sampling technique so that the sample consisted of 7 copra businesses. Data on the pattern of distribution of copra businesses were analyzed using nearest neighbor analysis, while for the feasibility of copra businesses were analyzed using the revenue cost ratio formula. The results of the study found that: (1) The pattern of distribution of copra businesses in Pesisir Selatan Regency has a pattern of spreading in three subdistricts, namely Lengayang District, Ranah District Coastal and Linggo Sari Baganti District. With the nearest neighbor analysis, the distance between the nearest neighbors and the distribution of copra businesses in Pesisir Selatan Regency is 2.123, a z-score is 5.684108 and a p-value is 0. (2) The feasibility of copra businesses spread across Pesisir Selatan Regency is obtained by the value of R/ The largest C is 5.21 while the lowest is 2.59 where the R/C value is > 1 which means that the copra business is feasible to run in Pesisir Selatan District.